A systematic study of laser ablation for space debris mitigation. Issue 1 (March 2017) - Battiston, R.; Burger, W.J.; Cafagna, A.; Manea, C.; Spataro, B.
Abstract: The increase in the number of artificial objects in orbit around the Earth represents a serious threat to the future utilization of space. The scope and nature of the problem require an international effort. The Trento Institute of Fundamental Physics and Applications (TIFPA) participates in a study of laser ablation for space applications, propulsion and space debris mitigation, in the context of the New Reflections program initiated by the Italian Institute of Nuclear Physics (INFN). An evaluation of the performance of laser ablation for debris removal in Low Earth Orbit (LEO), for different scenarios of ground and space-based lasers is presented. The ultimate aim is to provide a performance evaluation of the technology over the wide range of debris parameters, for both space-based and ground systems.